PERENCANAAN STRATEGIS SISTEM INFORMASI PENGUKURAN KINERJA DOSEN DENGAN MENGGUNAKAN IT-BALANCE SCORECARD - Gusti Syarifudin (SISFOTENIKA, 2013)
Abstract: Lecturer plays very important roles for the institutions of higher education because faculties have a role in the transfer of knowledge to the students. Besides teaching, Lecturer should conduct research and community service. To measure perfomance of lecturer include aspect education, research and community service. Data collection methods used was observation, interview and documentary study. To measurement performance of lecturer used of approach IT Balanced Scorecard. The IT Balanced Scorecard will analyze the performance of lecturers from four perspectives; the company's contribution, operational excellence, user orientation and future orientation. From lecturer performance measurement in this thesis is expected to be input for STMIK Pontianak in measuring lecturer performance.Keyword: Key Perfomance Indicator, Lecturer, IT-Balance Scorecard